2018
DOI: 10.1002/ajp.22866
|View full text |Cite
|
Sign up to set email alerts
|

High frequency/ultrasonic communication in a critically endangered nocturnal primate, Claire's mouse lemur (Microcebus mamiratra)

Abstract: The critically endangered Claire's mouse lemur, only found in the evergreen rain forest of the National Park Lokobe (LNP) and a few lowland evergreen rain forest fragments of northern Madagascar, was described recently. The present study provides the first quantified information on vocal acoustics of calls, sound associated behavioral context, acoustic niche, and vocal activity of this species. We recorded vocal and social behavior of six male-female and six male-male dyads in a standardized social-encounter p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…As dyads displaying high aggressive interaction rates showed respectively high Hiss call rates, it might be concluded that group members producing high Hiss rates are more aggressive and therefore more dominant than group members producing lower Hiss rates. This would fall in line with similar findings in other mammalian species where dominant group members exhibit higher call rates than subdominant ones (e.g., 65 69 ). Additionally, high defensive interaction rates showed a trend in predicting high Pant rates.…”
Section: Discussionsupporting
confidence: 91%
“…As dyads displaying high aggressive interaction rates showed respectively high Hiss call rates, it might be concluded that group members producing high Hiss rates are more aggressive and therefore more dominant than group members producing lower Hiss rates. This would fall in line with similar findings in other mammalian species where dominant group members exhibit higher call rates than subdominant ones (e.g., 65 69 ). Additionally, high defensive interaction rates showed a trend in predicting high Pant rates.…”
Section: Discussionsupporting
confidence: 91%
“…Arthropods were naturally available when they entered the cage. Observations were conducted between 6 p.m. and 9 p.m. for three consecutive nights (procedure matches to Hasiniaina et al, 2018). The observer sat 2–4 m in front of the cage wearing a dimmed headlamp while observing the animals.…”
Section: Methodsmentioning
confidence: 99%
“…Recorded files were audio‐screened with Audacity 2.2.2 and Batsound Pro 4.2. Across all studied species, the most common vocalization exchanged during agonistic conflicts was the so‐called Tsak call, recognizable by a uniform inverse U‐shaped frequency contour in the spectrograms (Hasiniaina et al, 2018; Zimmermann, 2010; Figure 2). Our analysis focused on this call type.…”
Section: Methodsmentioning
confidence: 99%
“…All animals were released after 1 week at their individual capture point after the end of the last night of observations. Such a temporary stay of wild mouse lemurs in cages has been employed in several previous experimental studies and adverse effects were not observed neither on the individual nor on the population level (e.g., [24, 51, 8083]).…”
Section: Methodsmentioning
confidence: 99%
“…The social encounter experiments were conducted in cages of about 1 m 3 that were equipped with four wooden bars and two sleeping sites (Fig. 8, [80]). Cages were placed in the forest close to the research camp but > 1 km away from the capture sites.…”
Section: Methodsmentioning
confidence: 99%